Modification of asphalt binder with various percentages of crumb rubber in flexible pavement - Altieb Ahmed, Zohair Ahmed (2016)
The scrap tires (crumb rubber) are being consumed every year, and these waste tires are generating environmental issue and causing health hazard due to burning this waste and increase the landfill space. The aim of the study is to use of crumb rubber in asphalt binder mix with penetration grade 80-100 and performance grade PG76. The asphalt binders were blended with waste crumb rubber in powder form 40 mesh (0.425 micron) using wet process. The study focused on the crumb rubber as partial replacement by (15, 20 and 25%) of total weight of modified asphalt binder mix. The laboratory works were based on American Society for Testing and Materials (ASTM) and (JKR/SPJ/2008-S4) standard of Malaysia, Several tests was conducted such as Penetration, Softening point, Viscosity, Rolling Thin Film Oven and Pressure Aging Vessel tests modified asphalt binder. The result shows positive effect in which the penetration decreases as the partial replacement of crumb rubber is increased 80-100 and PG76 blend asphalt binder. However, the PG76 asphalt binder result shows lower penetration in both short term and long term aging compared to 80-100 asphalt binder in term of stiffness. The results of softening point test show that percentage of replacement of asphalt binder with crumb rubber increases the temperature of 80-100 and PG76 asphalt binder mix, especially after short term aging (RTFOT) test of PG76 at 20% replacement the temperature reached 85°C and decreased after long term aging (PAV) test to 75°C. However, with partial replacement of asphalt binder with crumb rubber indicates resistance to higher temperature susceptibility. The viscosity test results conclude that the PG76 asphalt binder has higher viscosity compared to original PG76 and 80-100 asphalt binder replacement with crumb rubber mix. The PG76 asphalt binder indicates the 20% is the optimum crumb rubber replacement for short term aging (RTFOT) test. In the long term aging (PAV) test, the viscosity reduced compared with (RTFOT) test